Genetic polymorphisms as predictors of the response of hepatocellular carcinoma patients to doxorubicin chemotherapy: a genome-wide association study - Sireen Abdul Rahim Shilbayeh; Naglaa F. Khedr; Mohammad A. Alshabeeb; Abdulmonem Ali Alsaleh; Abdalrhman Hamdan Alanizi; Omnia A. Abd El-Baset; Rehab H. Werida (Frontiers in Pharmacology)
BackgroundHepatocellular carcinoma (HCC), a leading cause of cancer-related mortality, is commonly treated with doxorubicin (DOX). However, its effectiveness varies significantly among patients.AimThe present study aimed to identify potential genetic variants affecting the response of HCC patients to DOX.Methods78 patients with HCC who received DOX via transarterial chemoembolization (TACE) technology were selected. DNA was extracted from blood for genome-wide genotyping using the Applied Biosystems™ Axiom™ Precision Medicine Diversity Research™ Array. Genetic data were analysed using Axiom™ Analysis Suite software v5.2.ResultsSix hits in five genes [AK3 (rs378117), TRPM3 (rs1329774 and rs4745058), CDH4 (rs2427043), LINC00504 (rs76228864), and GRIN2D (rs76754767)] were associated with a risk of tumour progression, whereas variants in HPGD (rs45593131) and RC3H2 (rs2792999) were suggested as protective factors. rs8038528 in the PCSK6 gene was categorized as a low-response variant associated with an unsatisfactory reduction in α-fetoprotein (AFP) levels after DOX chemotherapy (P = 6.82 × 10−5). In contrast, three SNPs (rs1998853, rs12440990, and rs4774596) located within two genes (NPAS3 and DMXL2) were identified as predictors of good response rates to the treatment, as AFP levels were reduced by ≥ 20%. Death incidents showed associations with five SNPs that reached p ≤ 5.0 × 10−8; four of these are located within the DENND1B, LOC107986086, TMEM169, and RNF152 genes.ConclusionThese findings support the incorporation of pharmacogenomic testing into clinical practice for HCC therapy, paving the way for customized treatment methods that may improve therapeutic efficacy and patient outcomes. Future research is needed to replicate these genetic connections.